Money laundering problem: Responsibility of financial institutions - Fijat Ljiljana (Međunarodni Problemi, 2013)
The subject of this article is a specific problem in banking management - money laundering and financial institutions’ responsibility. Namely, at the beginning of the century, we were witnesses of global increase in money laundering. A lot of money earned by money laundering destroys the basic principles of economic activities. It is also a big threat to the financial institutions’ integrity making successful management impossible. Fundamental problems are as follows: “grey economy”, offshore countries and their financial institutions, corruption and alternative systems of transferring money. Therefore, their significance is emphasized in this article. All these dealings lead to general misuse of the financial systems. The connection between money laundering and financial terrorism is also considered. Terrorists’ needs can be classified to direct expenses connected to specific operations and to bigger organizing expenses for certain terrorist organizations as well as for the infrastructure maintenance in order to support the organization and promote the ideology of the particular terrorist organization. Money laundering can be used for these kinds of terrorist criminal activities. Some examples of misuse of banks, which were condemned for criminal acts, are also presented.